Role of Khadira Asana Sara Bhavita Triphala Churna in Atisthaulya - Aswathy, P; Godatwar, Pawan Kumar; Aravind , S (International Research Journal of Ayurveda & Yoga, 2021)
Objective: Athisthaulya (Obesity) has been mentioned among Ashtaninditha Purusha, one among the most hatred persons in the world. An obese man is feeling ashamed of his body size in the public, and thus Obesity turns to be a serious health concern. In the present-day life style, due to the advanced technology and busy work schedule, life has become more sedentary and variety of junk foods are ingested resulting in Atishtaulya. The potential of Ayurveda in tackling non-communicable diseases such as obesity wants to be explored as it contains an array of formulations. This article is an attempt to explore the causative factors, pathogenesis, symptomatology, and treatment modalities of Atisthaulya and to explain the role of Khadira Asana Sara Bhavitha Triphala Churna (Triphala Churna prepared by triturated with Kwatha of Khadira and Asana) in the management of Athisthaulya. Data source and Review methods: Data was collected through literature review of Classical Ayurvedic Literatures such as Charaka Samhita, Susruta Samhita, Astanga Hridaya and journal articles related to the subject, Conclusion: Atisthaulya is a disease in which mainly Kapha Dosha and Medas Dushya are involved which causes Medo-dhatvagnimandya (decreased fat digestion) and Srotas obstruction, ultimately causing abnormal Medo Dhatu Upacaya and then Staulya. In Khadira Asana Sara Bhavitha Triphala Churna and Medhoharaguggulu, most of the ingredients have Katu and Tikta Rasa, Ruksha, Laghu and Tikshna guna, Ushna Virya and Katu Vipaka, and Vata-Kaphasamaka property which may be effective to control Atisthaulya.